Rancang Bangun Pengendali Senjata SS1 Pemantau Keamanan Pos Perbatasan Berbasis Mikrokontroler - Rochmat Apriyanto; Abdul Rabi; Jeki Saputra; Irfan Mujahidin (Universitas Merdeka Malang, 2020)
The problem of borders between countries and between regions, both on land and at sea, is very complex. The current state of using security personnel at the border posts still has many limitations (human factor) in carrying out monitoring in the area of the border post. The guard post staff cannot fully carry out regional monitoring at the border post, as the visibility of each guard post staff member is still limited. As technology advances in the world, especially technology in the military, with the advent of upgrades in weapons control systems operating in automatic mode. This final design aims to develop the design or design of the SS1 weapons control system, which controls the security of border posts, automatically controls movements in azimuth and elevation. In this study, electronic control is used as an SS1 weapons control system to monitor the security of border posts. This tool is capable of moving 90˚ in azimuth and 15˚ in elevation to match the expected system of the tool.